PENGARUH PEMANFAATAN APLIKASI SHOPEE DALAM MENINGKATKAN PENJUALAN HYUNBINA COLLECTION - Laila Fitria; Zuhrinal M. Nawawi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
Indonesia is one of the countries whose residents have started using the internet in conducting buying and selling business transactions, with the increasing number of internet users and online business transactions, a marketplace, Shopee, was born. Shopee is an online marketplace platform that is used to practice buying and selling goods actively and easily. The products offered by this application are very diverse, ranging from garments, cellphones, beauty products, electronics, sports instruments, medicines, home furnishings, office stationery to food and beverages. Shopee services are implemented in interactions between producers and consumers quickly, easily and precisely. The advantages of Shopee are not only online business transactions, but Shopee is also a source of employment which is quite large and easy to work on. The sales strategy carried out by Shopee is very good so that this makes sellers and buyers more comfortable in shopping. The Shopee application is very suitable to be used as a sales medium because the promotional features provided by Shopee are able to increase the seller's sales profit. From the explanation above, the Hyunbina Collection business has a marketing method to sell products to consumers, it is necessary to use the Shopee Marketplace Sales to increase sales of women's bags. Based on the background of these problems, the authors are interested in compiling a Final Project report with the title "The Effect of Utilizing the Shopee Application in Increasing Sales of Hyunbina Collection".